Mengembangkan Kecerdasan Anak Usia Dini Melalui Pembelajaran Berbasis Pendidikan Kreatif - Sri Kadarwati; Budiharto Budiharto (Mukaddimah: Jurnal Studi Islam, 2018)
Quality education is the hope of us all, and all the nations in this world are competing to improve the quality of education. In order to improve the quality of education the Indonesian people are always working to make changes to the curriculum to address the changing times. Vice President Budiono is paying attention to education especially the 2013 curriculum, as we want to educate future generations that will be best, at least in 2035 or 32 years. According to him, which is prepared by the current government so that the future leaders of the nation are born they are still sitting in elementary to high school, because that’s what will be expected to be born gold generation.Early childhood is a group of children who are in the process of growth and development that is unique and is in the golden age, the time when children have a lot of excellent potential to be developed. One of the most important potential to be developed is the intelligence of children. Prof. Stenberg of Yale University states that there are three forms of intelligence that most people need to successfully run the role or work, namely intelligence analysis, creative intelligence, and contextual intelligence.In order to develop early childhood intelligence creative learning is applied. Creative can be defined as a set of abilities that reflect fluency, flexibility, and originality in thinking, as well as the ability to elaborate (develop, enrich, detail). In order to implement creative-based learning, teachers as education implementers should have four competencies, namely pedagogic competence, personality competence, social competence, and professional competence. These competencies are closely related to the quality of creativity and innovation of the teacher, both in conveying the material creatively in a creative model role model.Creative learning is very important to be developed by all teachers, because with creative learning will create an interesting climate, can be enjoyed by teachers and students, effective, efficient, and able to develop student potential or student intelligence. With the development of students’ intelligence, the learning will be more qualified and eventually the quality of education will be increased.